(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
Toponyms—geographical place names—serve as linguistic markers reflecting historical, cultural, and social transformations over time. This study examines the etymology of selected Uzbek toponyms, highlighting the diverse linguistic influences deriving from Turkic, Persian, Arabic, Mongolic, and Russian languages due to Uzbekistan’s rich historical interactions. Employing comparative linguistic methods combined with historical document analysis, this research deciphers the roots and evolution of place names in Uzbekistan. Findings underline the significance of toponyms as testimonies of the country’s multiethnic and multilingual heritage, enriching the field of onomastics and Central Asian studies.